Adaptive Strategies in a Poly-Extreme Environment: Differentiation of Vegetative Cells in Serratia ureilytica and Resistance to Extreme Conditions - Filippidou, Sevasti; Junier, Thomas; Wunderlin, Tina; Kooli, Wafa M.; Palmieri, Ilona; Al-Dourobi, Andrej; Molina, Veronica; Lienhard, Reto; Spangenberg, Jorge E.; Johnson, Shannon L.; Chain, Patrick S. G.; Dorador, Cristina; et al. (Frontiers in Microbiology, 2019)
Poly-extreme terrestrial habitats are often used as analogues to extra-terrestrial environments. Understanding the adaptive strategies allowing bacteria to thrive and survive under these conditions could help in the quest for extra-terrestrial planets suitable for life and understanding how life evolved in early earth conditions. A prime example of such a survival strategy is the modification of vegetative cells into resistant resting structures. These differentiated cells are often observed in response to harsh environmental conditions. The environmental strain (strain Lr5/4) belonging to Serratia ureilytica was isolated from a geothermal spring in Lirima, Atacama Desert, Chile. The geothermal spring from which the strain was isolated is oligotrophic and the temperature of 54°C exceeds mesophilic conditions (15 to 45oC). Although the vegetative cells were tolerant to various environmental insults (desiccation, extreme pH, glycerol), a modified cell type was formed in response to nutrient deprivation, UV radiation and thermal shock. Scanning (SEM) and Transmission Electron Microscopy (TEM) analyses of vegetative cells and the modified cell structures were performed. In SEM, a change towards a circular shape with reduced size was observed. These circular cells possessed what appears as extra coating layers under TEM. The resistance of the modified cells was also investigated, they were resistant to wet heat, UV radiation and desiccation, while vegetative cells did not withstand any of those conditions. A phylogenomic analysis was undertaken to investigate the presence of known genes involved in dormancy in other bacterial clades. Genes related to spore-formation in Myxococcus and Firmicutes were found in S. ureilytica Lr5/4 genome; however, these genes were not enough for a full sporulation pathway that resembles either group. Although, the molecular pathway of cell differentiation in S. ureilytica Lr5/4 is not fully defined, the identified genes may contribute to the modified phenotype in the Serratia genus. Here, we show that a modified cell structure can occur as a response to extremity in a species that was previously known not to deploy this strategy. This strategy may be widely spread in bacteria, but only expressed under poly-extreme environmental conditions.